Estrategias pedagógicas docentes para el abordaje de la dislexia del subnivel elemental, Escuela de Educación Básica Particular Estancia Pekes, Loja 2024 - Gómez Yanza, Gabriela Elizabeth (2024)
The present investigation had the general objective of establishing the incidence of pedagogical teaching strategies through a didactic proposal for addressing dyslexia in the elementary sublevel of the Estancia Pekes Private Basic Education School; it was a mixed study since it involved qualitative methods such as observation and quantitative methods such as the questionnaire, the pre and post test, of a descriptive type, quasi-experimental design, and cross- section. Questionnaires, pre and post tests were applied. The results found in the questionnaires are that teachers use the observation approach to identify learning difficulties, provide students with adapted materials, use teaching methods such as the multisensory approach and individualized support, likewise teachers promote self-esteem and confidence in students with dyslexia through the recognition and celebration of achievements, positive and constructive feedback, promote self-esteem and confidence in the classroom through participation and teamwork dynamics. In the teachers of the educational unit, the collaborative strategy and the multisensory strategy predominate. They work with the collaboration of the DECE to provide comprehensive support to students with dyslexia. The main challenges that the teacher presents are the lack of resources, the lack of support at home. The teacher evaluates the progress of the students through continuous monitoring, evaluates with curricular adaptation, through observation in the classroom and through formal and informal evaluations. The teacher, in order to improve his or her ability to support students with dyslexia more effectively: mentions that professional training and development, teaching materials and resources, specialized support and services, and finally interdisciplinary collaboration are necessary. On the other hand, the results found in the pre and post test are the following: Teachers know and handle teaching methodologies and techniques that benefit the learning of students with dyslexia. Within the techniques, the most used is active learning; They use technology and group work, even though the teachers were very familiar with the strategies for working with children with dyslexia, during the workshop this knowledge was reinforced and new techniques and strategies were made known. The teachers know and manage different programs or specific methodologies to support students with dyslexia in the learning process. Among the most used methodologies are active learning and discovery learning; even though the teachers apply appropriate methodologies in the classroom, at the end of the workshop there was an increase in the methodology of flipped learning and project-based learning. Finally, the teachers validate the workshop, since it allowed them to acquire new knowledge about pedagogical strategies regarding students with dyslexia.